ANALISIS KEUNTUNGAN DAN RISIKO USAHATANI TOMAT DI KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Neni Heriani; Wan Abbas Zakaria; Achdiansyah Soelaiman (Lampung University, 2013)
Tomato is one of the considerable potential agricultural products to be developed and cultivated because it has a high nutrition. In addition to its nutrients that are beneficial to health; tomatoes also provide some benefits to consumers, producers, and society. However, the fluctuative price of tomatoes at the producer level could affect the income received by farmers that arouse revenue risk. Therefore, it is necessary to study the farmers’ income and the level of tomato farm risk. The research was conducted in Argopeni Region Sumberejo Subdistrict of Tanggamus Regency. This location was chosen purposively. This research used a survey method in which 56 samples of this research were drawn by a simple random sampling. The analysis tool used for farmers’ income was R/C ratio; while the level of revenue risk was analyzed by calculating the variance, standard deviation and coefficient of variation. The research result showed that the value of R/C ratio was 3.03, it meant that the farming was profitable and viable. Meanwhile, based on the value of the coefficient variation that was 0.86, it showed that there was magnitude of risk faced by farmers and the lower earnings limit of tomato farm was Rp -5.985.235. This showed the amount loss that may be faced by the farmers if there were harm or risk. Keywords: coefficient variation, lower earnings limt, profit, risk, tomato farm